Physicochemical properties in NOR tomato line MA 131-6-3 after treated with ethephon and calcium carbide induced ripening - ALFASSABIQ KHAIRI; RUDI HARI MURTI; SITI NURUL ROFIQO IRWAN; EKA TARWACA SUSILA PUTRA (Society for Indonesian Biodiversity, 2023)
Abstract. Khairi A, Murti RH, Irwan SNR, Putra ETS. 2023. Physicochemical properties in NOR tomato line MA 131-6-3 after treated with ethephon and calcium carbide induced ripening. Biodiversitas 24: 3029-3037. Tomato fruit Postharvest Losses (PHL) from rotting, Physiological Weight Loss (PWL), inadequate nutrition, and other factors can lower fruit quality. Tomato is included as climacteric fruit which shows a significant increase in respiration and ethylene. The use of tomato with an extended shelf life due to genetic engineering, such as a Non-Ripening (NOR) tomato, can lower PHL. This experiment was carried out to evaluate physicochemical characteristics of NOR tomato fruit (lineMA 131-6-3 as result of selection F6)during postharvest after being treated by Ethephon (ET) (375, 750, 1,125, and 1,500 ppm), calcium carbide (CaC2) (5, 10, 15, and 20 gkg?1), and control. The experimental design was arranged in Randomized Completely Block Design with three replications.The ambient temperature was 28.30±1.75°C and relative humidity of 60.69±2.33%. The results showed the fruit ripening and physicochemical altered with CaC2 treatment, then followed by yellow but did not alter to the red color for all treatments. The value of reduction sugar, respiration, ethylene, PWL, and pH increased, meanwhile the fruit firmness decreased caused by CaC2. Furthermore, ET could increase rotting during storage.